2021
DOI: 10.1108/sampj-03-2019-0094
|View full text |Cite
|
Sign up to set email alerts
|

Imag(in)ing Colombian post-conflict in corporate sustainability reports

Abstract: Purpose This paper aims to study the use of photos in corporate sustainability reports (CSRs) as a means to gain legitimacy concerning Colombian post-conflict representations. Design/methodology/approach From a critical perspective based on legitimacy theory and political economy theory, and using visual semiotics and critical discourse analysis, this paper examines the use of photographs in sustainability reports as a mechanism to account for corporate actions regarding peace in Colombia. This paper relies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…While denotation represents the simple aspects of every visual image (people, products and things), connotation codes symbolic meanings (Davison and Warren, 2017). For example, Barthes (1964) demonstrates that, while images of peppers, tomatoes and certain other vegetables indicate what they are on a connotation level, their combination denotes a symbolic message of “Italianicity.” Hrasky (2012) draws a similar conclusion, claiming that some businesses seek pragmatic legitimacy through the use of persuasive visual elements, such as images, to portray and market themselves as responsible corporate citizens (also see Cabrera-Narváez and Quinche-Martín, 2021). For example, by depicting beautiful natural landscapes, community imagery and happy employees, the corporation seeks to portray itself as a caring and committed corporate citizen.…”
Section: Literature Reviewmentioning
confidence: 89%
“…While denotation represents the simple aspects of every visual image (people, products and things), connotation codes symbolic meanings (Davison and Warren, 2017). For example, Barthes (1964) demonstrates that, while images of peppers, tomatoes and certain other vegetables indicate what they are on a connotation level, their combination denotes a symbolic message of “Italianicity.” Hrasky (2012) draws a similar conclusion, claiming that some businesses seek pragmatic legitimacy through the use of persuasive visual elements, such as images, to portray and market themselves as responsible corporate citizens (also see Cabrera-Narváez and Quinche-Martín, 2021). For example, by depicting beautiful natural landscapes, community imagery and happy employees, the corporation seeks to portray itself as a caring and committed corporate citizen.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Analysing photographic content in corporate reports, Boiral (2013) found an abundance of positive, idealized representations that are disconnected from reality, implying companies’ intention to inflate corporate legitimacy and reputation. Cabrera-Narváez and Quinche-Martín (2020) also showed that photographs are used by firms as a visual form of representing corporate peace action in sustainability reports in contexts where it is precarious. These findings are supported by Ali et al (2021) who found that photographs predominately signal positive sustainability messages.…”
Section: Attribute Framing With Photographsmentioning
confidence: 99%
“…Although prior studies have addressed the ability of photographs to convey complex messages and elusive meanings (e.g. Breitbarth et al , 2010; Pesci et al , 2015; Rämö, 2011; Cabrera-Narváez and Quinche-Martín, 2020), it remains unclear which features of photographs are used to capture attention and evoke specific emotions in the context of sustainability reporting. This is important because Boiral (2013) found an abundance of positive and idealized photographic content in sustainability reports, suggesting that companies strive to present themselves with “a socially responsible image so that they can legitimize their behaviors to stakeholder groups and influence the external perception of reputation” (Branco and Rodrigues, 2008, p. 686).…”
Section: Introductionmentioning
confidence: 99%
“…En 2017 se publicaron dos trabajos de contabilidad social y ambiental (Macías & Farfán-Liévano, 2017;Sinforoso et al, 2017) y a partir de ellos fueron surgiendo otros artículos en importantes revistas internacionales. El mayor grupo es sobre contabilidad no financiera (Cabrera-Narváez & Quinche-Martín, 2021;Correa-García et al, 2020;Quinche-Martín & Cabrera-Narváez, 2020), pero también hay otros trabajos muy destacados sobre historia de la contabilidad (Quintero, 2020;Rico-Bonilla, 2020), la relación contabilidad y género (Chamorro et al, 2020;Rico-Bonilla, 2020), covid-19 (Alba-Cabañas & Gómez, 2021Gómez & Alba-Cabañas, 2020;Sangster et al, 2020), sobre contabilidad gubernamental (León-Silva et al, 2020;Ocampo-Salazar, 2020) y sobre contabilidad de gestión (Barrios Álvarez et al, 2021).…”
Section: Integración Con Las Discusiones Extrarregionalesunclassified